Preparation method and application of monatomic iron-loaded catalyst based on nanocellulose hierarchical porous carbon aerogel
By using nanocellulose multi-stage pore carbon aerogel to load single-atom iron catalyst in zinc air batteries, the problems of complex kinetics of oxygen reduction reactions and high cost of platinum-based materials in zinc air batteries are solved, and efficient and stable oxygen is achieved Reduction catalytic performance and long-term electrocatalyst stability.
Patent Information
- Application Number
- CN202411315663.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-20
AI Technical Summary
The kinetics of the air cathode oxygen reduction reaction of existing zinc air batteries are complex and slow, and the cost of platinum-based precious metal materials is high, resources are scarce and easy to be inactivated. The active sites of non-precious metal catalysts such as M-N-C materials are insufficient, resulting in their catalysis. The performance is still different from that of platinum-based catalysts, and the preparation process of single-atom catalysts is complex and difficult to control.
The preparation method based on nanocellulose multi-stage porous carbon aerogel supports single-atom iron catalyst, and the TOCNFs-Cd2+/Fe2+ hydrogel is formed by reacting oxidized nanocellulose fibers with metal salt solution, and carbonized at high temperature after freeze-drying. Synthesize nitrogen-doped multi-stage porous carbon-loaded single-atom ferrooxygen reduction electrocatalyst to form Fe-N4 active sites, improving the activity and stability of the catalyst.
It achieves efficient catalytic performance and long-term stability of oxygen reduction reaction, meets the economical, green and efficient electrocatalytic materials needs, and is simple in preparation, low in cost and environmentally friendly.
Smart Images

Figure CN119170816A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of single-atom catalysts, and specifically relates to a preparation method and application of a single-atom iron catalyst supported on nanocellulose multi-level porous carbon aerogel. Background Art
[0002] Zinc-air batteries are a new type of electrochemical energy conversion device due to their high energy density, low manufacturing cost, high safety, and environmental protection. However, the main obstacle to their commercial application comes from the complex and slow reaction kinetics of the oxygen reduction reaction (ORR) at the air cathode. Although platinum-based precious metal materials are widely used as efficient ORR electrocatalysts, their high cost, scarce resources, and easy deactivation limit their commercial use. Therefore, researchers have turned to the development of non-precious metal catalysts, especially metal-loaded nitrogen-doped carbon (M–N–C, M=Fe, Co, etc.) composites. However, due to insufficient active sites, the catalytic performance of M–N–C materials is still far behind that of the most advanced platinum-based catalysts.
[0003] M–N–C catalysts with metal sites dispersed in the form of single atoms on carbon supports have attracted extensive research interest and exhibited excellent ORR electrocatalytic activity. Theoretical studies have shown that the precise regulation of Fe–N x The presence of monodisperse metal sites in the form of geometric structures can induce an inhomogeneous distribution of charge, which is beneficial to the adsorption of O2 and intermediates and the subsequent O=O bond cleavage. In addition to the coordination environment, the performance of single-atom catalysts depends largely on the number of effective metal sites exposed on the carbon support. However, due to the embedding effect of the carbon support, the morphology and microstructure of the carbon may limit the actual utilization efficiency of the metal sites. Another issue of concern is that during the direct pyrolysis process, metals have a tendency to agglomerate due to their high surface energy, which makes the precise control of monodisperse metal atoms extremely difficult.
[0004] Therefore, the preparation of single-atom catalysts usually involves the careful selection and structural optimization of metal / nitrogen precursors and carbon supports, as well as tedious acid etching and subsequent heat treatment processes. These traditional methods usually lead to uncontrollable local environments of metal sites and cannot truly achieve atom economy, making the large-scale production and practical application of single-atom catalysts more difficult.
[0005] Stably loading metal single atoms on hierarchical porous carbon supports is an effective strategy to achieve maximum utilization of metal sites. In particular, rationally constructed ultra-low density, ultra-large specific surface area three-dimensional carbon aerogels are effective carriers of single atoms, which are conducive to fully exposing active sites and improving the utilization of metal atoms. At the same time, its three-dimensional porous and network structure is also very beneficial for accelerating the material and electron transport at the three-phase boundary (catalyst-electrolyte-oxygen). However, due to the insufficient interaction between metal and carbon support, it is still a huge challenge to accurately anchor metal single atoms to carbon aerogels.
[0006] Therefore, it is of great significance to use a greener and more sustainable method to prepare porous carbon aerogel-supported metal single atom catalysts and optimize and regulate their catalytic performance. Summary of the invention
[0007] In order to overcome the problems of the above prior art, the purpose of the present invention is to provide a preparation method and application of a single-atom iron catalyst supported on a nanocellulose multi-level porous carbon aerogel, introducing single-atom iron into a nitrogen-doped carbon aerogel with a highly hierarchical pore structure, prompting it to form Fe-N4 active sites with N, thereby giving a higher density of active sites, achieving effective mass transfer / electron transfer, and improving catalytic reaction activity. The steps are simple, the cost is low, and there is no pollution to the environment. The prepared catalyst has excellent ORR catalytic performance and long-term stability.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A nanocellulose hierarchical porous carbon aerogel-supported single-atom iron catalyst was prepared using oxidized nanocellulose fibrils (TOCNFs) as precursors. 2+ / Fe 2+ The hydrogel selectively volatilizes Cd during the pyrolysis process, and the doped N forms single-atom Fe-N4 active sites with the retained Fe to synthesize nitrogen-doped hierarchical porous carbon-supported single-atom iron oxygen reduction electrocatalyst. The catalyst has a three-dimensional cross-linked network, rich microporous structure and ultra-high specific surface area, and the iron single-atom sites are anchored in the three-dimensional hierarchical pores and rich microporous defects.
[0010] A method for preparing a nanocellulose-based multi-level porous carbon aerogel-supported single-atom iron catalyst comprises the following steps:
[0011] Step 1: Sol-gel method to 2+ / Fe 2+ The metal salt solution reacts with the TOCNFs suspension, and after solvent exchange, TOCNFs-Cd 2+ / Fe 2+ Hydrogel;
[0012] Step 2: The TOCNFs-Cd 2+ / Fe 2+ The hydrogel was freeze-dried to obtain TOCNFs-Cd 2+ / Fe 2+ Aerogel;
[0013] Step 3: The TOCNFs-Cd 2+ / Fe 2+ The aerogel was placed in a quartz boat and placed in the center of the tube furnace. At the same time, the quartz boat containing NH4Cl powder was placed between the air inlet of the tube furnace and the quartz boat containing TOCNFs-Cd 2+ / Fe 2+ Nitrogen-doped hierarchical porous carbon-supported single-atom iron oxygen reduction electrocatalyst was synthesized by high-temperature carbonization in an inert gas environment between the quartz boats of aerogel.
[0014] In the metal salt solution in step 1, Cd 2+ / Fe 2+ The molar ratio is 10:1 to 10000:1.
[0015] The metal salt solution in the step 1 is a cadmium chloride hemi(pentahydrate) solution and a ferrous acetate solution;
[0016] The mass ratio of TOCNFs to metal salt (cadmium chloride hemi(pentahydrate) and ferrous acetate) in step 1 is 1:1 to 1:50.
[0017] The TOCNFs-Cd in step 2 2+ / Fe 2+ The freeze-drying temperature of the gel is -20 to -53°C and the time is 24 to 48 hours, so that the hydrogel is fully dried and its internal three-dimensional skeleton network is maintained.
[0018] The mass of NH4Cl powder in step 3 is 10-15g;
[0019] The inert gas used in step three is argon.
[0020] The high-temperature carbonization temperature in step 3 is 600-800°C, the holding time is 1-2h, and the heating rate of the tubular furnace is 1-5°C / min. The carbonization temperature set at 800°C can achieve carbonization of cellulose, and at the same time, the cross-linking agent Cd metal is fully volatilized, which is conducive to the formation of abundant micropores and defect structures in the carbon aerogel.
[0021] The nitrogen-doped multi-level porous carbon-supported single-atom iron oxygen reduction electrocatalyst is applied to zinc-air batteries. By removing the volatile metal Cd and introducing an additional nitrogen source, the iron single atom is loaded on the nitrogen-doped carbon nanofiber aerogel in the form of Fe-N4 coordination; the ultra-high porosity of the carbon aerogel is conducive to fully exposing the active metal atom sites during the electrocatalytic process, and the three-dimensional network structure is conducive to achieving rapid mass and electron transfer.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention selects oxidized nanocellulose fibrils (TOCNFs) extracted from wood cellulose as precursors. The raw materials are widely available and green and environmentally friendly. The naturally interconnected nanoscale fiber network gives it significant structural advantages. The fibrous TOCNFs are rich in hydroxyl and carboxyl groups and can react with Cd-containing 2+ / Fe 2+ The metal salt solution undergoes a cross-linking reaction to form TOCNFs-Cd 2+ / Fe 2+ Hydrogel.
[0024] (2) During the high-temperature carbonization process, the low-boiling-point metal Cd (767°C) volatilizes when heated and generates a large number of micropores through the "endogenous pore-forming" effect, which provides space for anchoring catalytic active sites and the transmission and diffusion of reactants. At the same time, Fe atoms form Fe-N4 coordination bonds with doped N, successfully constructing active sites for catalytic reactions.
[0025] (3) The prepared nitrogen-doped multi-level porous carbon-supported single-atom iron oxygen reduction electrocatalyst not only has an ultra-high specific surface area and a multi-level pore structure, but also is rich in a large number of exposed reaction active centers and has excellent ORR electrocatalytic performance, meeting the application requirements of synthesizing economical, green and efficient electrocatalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope (SEM) image of the electrocatalyst of Example 4 of the present invention.
[0027] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of the electrocatalyst of Example 4 of the present invention.
[0028] Figure 3 This is a comparison chart of the LSV curves of the electrocatalysts of Example 4 of the present invention, Comparative Examples 1 and 2, and a commercial Pt / C catalyst in an alkaline medium.
[0029] Figure 4 This is a stability comparison chart of the electrocatalyst of Example 4 of the present invention and a commercial Pt / C catalyst in an alkaline medium.
[0030] Figure 5 The charge and discharge polarization curve and power curve of the zinc-air battery assembled with the electrocatalyst of Example 4 of the present invention as the air electrode material. DETAILED DESCRIPTION
[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0032] Example 1
[0033] This embodiment provides a method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst, which is prepared by the following steps:
[0034] Step 1: Add 0.5 molCd 2+ and 50mmolFe 2+ The metal salt solution was slowly added into the evenly dispersed TOCNFs suspension and allowed to stand at room temperature for 24 h to obtain TOCNFs-Cd 2+ / Fe 2+ hydrogel, and then 100 mL of tert-butyl alcohol solution was mixed with TOCNFs-Cd 2+ / Fe 2+ The water in the hydrogel was solvent replaced and allowed to stand at room temperature for 24 h to prepare TOCNFs-Cd 2+ / Fe 2+ gel.
[0035] Step 2: The TOCNFs-Cd obtained in step 1 2+ / Fe 2+ The gel was freeze-dried at -20 °C for 48 h to obtain TOCNFs-Cd 2+ / Fe 2+ Aerogel.
[0036] Step 3: The TOCNFs-Cd obtained in step 2 2+ / Fe 2+ The aerogel was placed in a quartz boat and placed in the center of the tube furnace. At the same time, a quartz boat containing 10 g NH4Cl powder was placed between the air inlet of the tube furnace and the quartz boat containing TOCNFs-Cd 2+ / Fe 2+ The temperature was raised to 600°C at a rate of 1°C / min in an argon gas environment, kept for 1 hour and then naturally cooled to room temperature to prepare a nitrogen-doped multi-level porous carbon-supported single-atom iron oxygen reduction electrocatalyst.
[0037] Example 2
[0038] This embodiment provides a method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst, which is prepared by the following steps:
[0039] Step 1: Add 0.5 molCd 2+ and 5mmolFe 2+ The metal salt solution was slowly added into the evenly dispersed TOCNFs suspension and allowed to stand at room temperature for 24 h to obtain TOCNFs-Cd 2+ / Fe 2+ hydrogel, and then 100 mL of tert-butyl alcohol solution was mixed with TOCNFs-Cd 2 + / Fe 2+ The water in the hydrogel was solvent replaced and allowed to stand at room temperature for 24 h to prepare TOCNFs-Cd 2+ / Fe 2+ gel.
[0040] Step 2: The TOCNFs-Cd obtained in step 1 2+ / Fe 2+ The gel was freeze-dried at -35 °C for 48 h to obtain TOCNFs-Cd 2+ / Fe 2+ Aerogel.
[0041] Step 3: The TOCNFs-Cd obtained in step 2 2+ / Fe 2+ The aerogel was placed in a quartz boat and placed in the center of the tube furnace. At the same time, a quartz boat containing 12 g NH4Cl powder was placed between the air inlet of the tube furnace and the quartz boat containing TOCNFs-Cd 2+ / Fe 2+ The temperature was raised to 700°C at a heating rate of 2°C / min in an argon gas environment, kept for 1 hour and then naturally cooled to room temperature to prepare a nitrogen-doped multi-level porous carbon-supported single-atom iron oxygen reduction electrocatalyst.
[0042] Example 3
[0043] This embodiment provides a method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst, which is prepared by the following steps:
[0044] Step 1: Add 0.5 molCd 2+ and 0.5mmolFe 2+ The metal salt solution was slowly added into the evenly dispersed TOCNFs suspension and allowed to stand at room temperature for 24 h to obtain TOCNFs-Cd 2+ / Fe 2+ hydrogel, and then 100 mL of tert-butyl alcohol solution was mixed with TOCNFs-Cd 2+ / Fe 2+ The water in the hydrogel was solvent replaced and allowed to stand at room temperature for 24 h to prepare TOCNFs-Cd 2+ / Fe 2+gel.
[0045] Step 2: The TOCNFs-Cd obtained in step 1 2+ / Fe 2+ The gel was freeze-dried at -40 °C for 36 h to obtain TOCNFs-Cd 2+ / Fe 2+ Aerogel.
[0046] Step 3: The TOCNFs-Cd obtained in step 2 2+ / Fe 2+ The aerogel was placed in a quartz boat and placed in the center of the tube furnace. At the same time, a quartz boat containing 12 g NH4Cl powder was placed between the air inlet of the tube furnace and the quartz boat containing TOCNFs-Cd 2+ / Fe 2+ The temperature was raised to 750°C at a rate of 2°C / min in an argon gas environment, kept for 1 hour and then naturally cooled to room temperature to prepare a nitrogen-doped multi-level porous carbon-supported single-atom iron oxygen reduction electrocatalyst.
[0047] Example 4
[0048] This embodiment provides a method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst, which is prepared by the following steps:
[0049] Step 1: Add 0.5 molCd 2+ and 0.05mmolFe 2+ The metal salt solution was slowly added into the evenly dispersed TOCNFs suspension and allowed to stand at room temperature for 24 h to obtain TOCNFs-Cd 2+ / Fe 2+ hydrogel, and then 100 mL of tert-butyl alcohol solution was mixed with TOCNFs-Cd 2+ / Fe 2+ The water in the hydrogel was solvent replaced and allowed to stand at room temperature for 24 h to prepare TOCNFs-Cd 2+ / Fe 2+ gel.
[0050] Step 2: The TOCNFs-Cd obtained in step 1 2+ / Fe 2+ The gel was freeze-dried at -53 °C for 48 h to obtain TOCNFs-Cd 2+ / Fe 2+ Aerogel.
[0051] Step 3: The TOCNFs-Cd obtained in step 2 2+ / Fe 2+The aerogel was placed in a quartz boat and placed in the center of the tube furnace. At the same time, a quartz boat containing 15 g NH4Cl powder was placed between the air inlet of the tube furnace and the quartz boat containing TOCNFs-Cd 2+ / Fe 2+ The temperature was raised to 800°C at a heating rate of 5°C / min in an argon gas environment, kept for 2 hours and then naturally cooled to room temperature to prepare a nitrogen-doped multi-level porous carbon-supported single-atom iron oxygen reduction electrocatalyst.
[0052] Comparative Example 1
[0053] This comparative example provides a method for preparing a nitrogen-doped porous carbon oxygen reduction electrocatalyst based on nanocellulose, which is prepared by the following steps:
[0054] Step 1: Slowly add a solution containing 0.5 mol HCl into the evenly dispersed TOCNFs suspension and let it stand at room temperature for 24 h to obtain TOCNFs-H + hydrogel, and then 100 mL of tert-butyl alcohol solution was mixed with TOCNFs-H + The water in the hydrogel was solvent replaced and allowed to stand at room temperature for 24 h to prepare TOCNFs-H + gel.
[0055] Step 2: The TOCNFs-H obtained in step 1 + The gel was freeze-dried at -53 °C for 48 h to obtain TOCNFs-H + Aerogel.
[0056] Step 3: The TOCNFs-H obtained in step 2 + The aerogel was placed in a quartz boat and placed in the center of the tube furnace. At the same time, a quartz boat containing 10 g NH4Cl powder was placed between the air inlet of the tube furnace and the quartz boat containing TOCNFs-H + The temperature was raised to 800°C at a heating rate of 5°C / min in an argon gas environment, kept for 2 hours and then naturally cooled to room temperature to prepare a nitrogen-doped porous carbon oxygen reduction electrocatalyst.
[0057] Comparative Example 2
[0058] This comparative example provides a method for preparing a nitrogen-doped multi-level porous carbon oxygen reduction electrocatalyst based on nanocellulose, which is prepared by the following steps:
[0059] Step 1: Add 0.5 molCd 2+ The metal salt solution was slowly added into the evenly dispersed TOCNFs suspension and allowed to stand at room temperature for 24 h to obtain TOCNFs-Cd 2+ hydrogel, and then 100 mL of tert-butyl alcohol solution was mixed with TOCNFs-Cd 2+The water in the hydrogel was solvent replaced and allowed to stand at room temperature for 24 h to prepare TOCNFs-Cd 2+ gel.
[0060] Step 2: The TOCNFs-Cd obtained in step 1 2+ The gel was freeze-dried at -53 °C for 48 h to obtain TOCNFs-Cd 2+ Aerogel.
[0061] Step 3: The TOCNFs-Cd obtained in step 2 2+ The aerogel was placed in a quartz boat and placed in the center of the tube furnace. At the same time, a quartz boat containing 10 g NH4Cl powder was placed between the air inlet of the tube furnace and the quartz boat containing TOCNFs-Cd 2+ The temperature was raised to 800°C at a heating rate of 5°C / min in an argon gas environment, kept for 2 hours and then naturally cooled to room temperature to prepare a nitrogen-doped multi-level porous carbon oxygen reduction electrocatalyst.
[0062] Test Example 1:
[0063] The nitrogen-doped multi-level porous carbon-supported single-atom iron-oxygen reduction electrocatalyst prepared in Example 4 was tested by scanning electron microscopy and high-resolution transmission electron microscopy. The results are as follows: Figure 1 , Figure 2 shown.
[0064] according to Figure 1 It can be seen that the three-dimensional nanostructure of Example 4 is composed of evenly dispersed fibers with a fiber diameter of about 15 nm. The distribution of pores of different sizes between the fibers is mainly attributed to the positive effect of the introduction of Cd on the maintenance and optimization of the nanofiber pore structure. Figure 2 It can be observed that a large number of iron atom bright spots marked with red circles are evenly distributed on the fiber.
[0065] Test Example 2
[0066] ORR test and stability test of Example 4, Comparative Examples 1 and 2 and commercial Pt / C catalysts in the present invention.
[0067] The electrochemical test was carried out using a three-electrode system. 10 mg of the electrocatalyst was dispersed in an ethanol / Nafion mixture (volume ratio of 48:2), followed by ultrasonic treatment to form a homogeneous catalyst suspension. Then 8 μL of the catalyst suspension was dropped onto a glassy carbon electrode with a diameter of 5 mm. The reference electrode was an Ag / AgCl electrode and the counter electrode was a platinum sheet. The electrolyte used in the ORR test and stability test was an oxygen-saturated 0.1 M potassium hydroxide solution.
[0068] like Figure 3As shown in the figure, the LSV curve comparison of the electrocatalysts of Example 4 of the present invention, Comparative Examples 1 and 2 and the commercial Pt / C electrocatalyst in alkaline medium shows that the half-wave potential of Example 4 is 0.855 V, which is significantly better than that of Pt / C (E onset =0.95V, E 1 / 2 =0.841V), Comparative Example 1 (E onset =0.91V, E 1 / 2 =0.823V) and control example 2 (E onset =0.93V, E 1 / 2 =0.836V).
[0069] like Figure 4 As shown, this is a stability comparison diagram of the electrocatalyst of Example 4 of the present invention and the commercial Pt / C electrocatalyst in an alkaline medium. It can be seen that the retention rate of Example 4 in the cyclic stability test of up to 14 hours is as high as 85%, showing stronger stability than the commercial Pt / C electrocatalyst (79%).
[0070] Test Example 3
[0071] The nitrogen-doped multi-level porous carbon-supported single-atom iron oxygen reduction electrocatalyst in Example 4 of the present invention is applied to zinc-air batteries
[0072] 2.5 mg of the catalyst was mixed with a dispersant ethanol / deionized water mixture (volume ratio of 1:1), and then a binder Nafion was added, and the volume ratio of the dispersant to the binder was 1:500. The homogeneous catalyst suspension formed after ultrasonic dispersion was dripped onto the treated carbon cloth to form a cathode electrode. The polished zinc sheet was used as the anode of the zinc-air battery, the cathode electrode prepared by the present invention was used as the cathode, and a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate was used as the electrolyte solution.
[0073] like Figure 5 As shown in the figure, the charge and discharge polarization curve and power curve of the zinc-air battery assembled with the electrocatalyst of Example 4 as the air electrode material of the present invention, it can be seen that the power density of the battery assembled with the electrocatalyst of Example 4 can reach 206mWcm -2 , which is superior to the commercial Pt / C-RuO2 catalyst.
Claims
1. A nanocellulose-based multi-level porous carbon aerogel-supported single-atom iron catalyst, characterized in that: Preparation of TOCNFs-Cd using oxidized nanocellulose fibrils (TOCNFs) as precursor 2+ / Fe 2+ The hydrogel selectively volatilizes Cd during the pyrolysis process, and the doped N forms single-atom Fe-N4 active sites with the retained Fe to synthesize nitrogen-doped hierarchical porous carbon-supported single-atom iron oxygen reduction electrocatalyst. The catalyst has a three-dimensional cross-linked network, rich microporous structure and ultra-high specific surface area, and the iron single-atom sites are anchored in the three-dimensional hierarchical pores and rich microporous defects.
2. The method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst according to claim 1, characterized in that: The steps include: Step 1: Sol-gel method to 2+ / Fe 2+ The metal salt solution reacts with the TOCNFs suspension, and after solvent exchange, TOCNFs-Cd 2+ / Fe 2+ Hydrogel; Step 2: The TOCNFs-Cd 2+ / Fe 2+ The hydrogel was freeze-dried to obtain TOCNFs-Cd 2+ / Fe 2+ Aerogel; Step 3: The TOCNFs-Cd 2+ / Fe 2+ The aerogel was placed in a quartz boat and placed in the center of the tube furnace. At the same time, the quartz boat containing NH4Cl powder was placed between the air inlet of the tube furnace and the quartz boat containing TOCNFs-Cd 2+ / Fe 2+ Nitrogen-doped hierarchical porous carbon-supported single-atom iron oxygen reduction electrocatalyst was synthesized by high-temperature carbonization in an inert gas environment between the quartz boats of aerogel.
3. The method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst according to claim 2, characterized in that: In the metal salt solution in step 1, Cd 2+ / Fe 2+ The molar ratio is 10:1 to 10000:
1.
4. The method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst according to claim 2, characterized in that: The metal salt solution in the step 1 is a cadmium chloride hemi(pentahydrate) solution and a ferrous acetate solution; The mass ratio of TOCNFs to metal salt (cadmium chloride hemi(pentahydrate) and ferrous acetate) in step 1 is 1:1 to 1:
50.
5. The method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst according to claim 2, characterized in that: The TOCNFs-Cd in step 2 2+ / Fe 2+ The freeze-drying temperature of the gel is -20 to -53°C and the time is 24 to 48 hours.
6. The method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst according to claim 2, characterized in that: The mass of the NH4Cl powder in step 3 is 10-15 g.
7. The method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst according to claim 2, characterized in that: The inert gas used in step three is argon.
8. The method for preparing a nanocellulose multi-level porous carbon aerogel-supported single-atom iron catalyst according to claim 2, characterized in that: The high-temperature carbonization temperature in step three is 600-800° C., the insulation time is 1-2 hours, and the heating rate of the tubular furnace is 1-5° C. / min.
9. Use of the nanocellulose-based multi-level porous carbon aerogel-supported single-atom iron catalyst prepared by the method according to any one of claims 2 to 8, characterized in that: The catalyst is applied to zinc-air batteries. By removing the volatile metal Cd and introducing an additional nitrogen source, the iron single atom is loaded on the nitrogen-doped carbon nanofiber aerogel in the form of Fe-N4 coordination; the ultra-high porosity of the carbon aerogel is conducive to fully exposing the active metal atom sites during the electrocatalytic process, and the three-dimensional network structure is conducive to achieving rapid mass and electron transfer.
Citation Information
Cited By
Nitrogen-doped carbon-lithium-sulfur battery positive electrode carrier material with directional pore channels and iron monatomic anchoring and preparation method and application of nitrogen-doped carbon-lithium-sulfur battery positive electrode carrier material
CN122343964A
